Carotenoid metabolism: New insights and synthetic approaches - Stra, Alice; Almarwaey, Lamyaa O.; Alagoz, Yagiz; Moreno, Juan C.; Al-Babili, Salim (Frontiers in Plant Science, 2023)
Carotenoids are well-known isoprenoid pigments naturally produced by plants, algae, photosynthetic bacteria as well as by several heterotrophic microorganisms. In plants, they are synthesized in plastids where they play essential roles in light-harvesting and in protecting the photosynthetic apparatus from reactive oxygen species (ROS). Carotenoids are also precursors of bioactive metabolites called apocarotenoids, including vitamin A and the phytohormones abscisic acid (ABA) and strigolactones (SLs). Genetic engineering of carotenogenesis made possible the enhancement of the nutritional value of many crops. New metabolic engineering approaches have recently been developed to modulate carotenoid content, including the employment of CRISPR technologies for single-base editing and the integration of exogenous genes into specific “safe harbors” in the genome. In addition, recent studies revealed the option of synthetic conversion of leaf chloroplasts into chromoplasts, thus increasing carotenoid storage capacity and boosting the nutritional value of green plant tissues. Moreover, transient gene expression through viral vectors allowed the accumulation of carotenoids outside the plastid. Furthermore, the utilization of engineered microorganisms allowed efficient mass production of carotenoids, making it convenient for industrial practices. Interestingly, manipulation of carotenoid biosynthesis can also influence plant architecture, and positively impact growth and yield, making it an important target for crop improvements beyond biofortification. Here, we briefly describe carotenoid biosynthesis and highlight the latest advances and discoveries related to synthetic carotenoid metabolism in plants and microorganisms.